International Migration and Trade Agreements: the new role of PTAs - Gianluca Orefice (FIW - Research Centre International Economics, 2013)
This paper investigates empirically the role of Preferential Trade Agreements (PTAs) as determinants of migration inflows for 29 OECD countries in the period 1998-2008. By increasing information about signatory countries, PTAs are expected to drive migration flows towards member countries. Building on the empirical literature on the determinants of migration, I estimate a modified gravity model on migration flows providing evidence of a strong positive effect of PTAs on bilateral migration flows. I also consider the content of PTAs as a further determinant of migration, finding that visa-and-asylum and labour market related provisions, when included in PTAs, stimulate bilateral migration flows. Finally, by comparing the average effects of PTAs on migration flows and on trade, I show that PTAs stimulate bilateral migration flows more than trade in final goods. PTAs might be used by government to increase inflows of immigrant workers in the case of labour shortages or population ageing.
Keywords: F22; F13; F53; F16; 330; International Migration; Trade Policy; Migration Policy; PTAs